Effect of infection with gonococci on myeloperoxidase activity of leucocytes. - Schultz, W W (1975)
Lyosomal myeloperoxidase activity in human phagocytic leucocytes was stimulated by incubation with virulent (T1) and avirulent (T4) forms of Neisseria gonorrhoeae. The amount of activity, assayed by bacterial iodination (125-iodine) after 30 min. exposure to the pagocytes in the absence of serum, was about fifty times greater in cells infected with T4 strains. In the presence of heated human serum, or its IgG component, myeloperoxidase activity increased, but T1-Stimulated activity was significantly less than that of T4 and was not proportional to multiplicity of infection. From these results and from those of a previous study we conclude that T1 can stimulate leucocyte myeloperoxidase activity from an extracellular location, that for this activity a serum fraction is required, and that this may be a mechanism responsible for some of the killing of the membrane associated T1.